Performance Evaluation of Reducing Consumption of Energy in the Yangtze River Delta under the Background of Low-Carbon Economy - Chenguang Sun; Bo Miao (Journal of Mathematics)
With global climate change and rapid environmental degradation, reducing energy consumption has attracted widespread attention worldwide. The Yangtze River Delta is a major province in China in terms of energy consumption and pollutant emissions. After adopting a series of energy-saving and emission-reduction measures, the Yangtze River Delta has achieved certain results. However, at present, the Yangtze River Delta region has a serious heavy industrial structure and many “two high and one capital” industries, which play a huge role in driving GDP growth. This situation will inevitably aggravate the contradiction between the three systems of energy, environment, and economy. In this context, a scientific and reasonable evaluation of the performance of reducing energy consumption and further promoting the implementation of reducing energy consumption in the Yangtze River Delta. It is conducive to achieving low carbon and energy conservation in the Yangtze River Basin provinces. In order to comprehensively examine and evaluate the consumption reduction performance of the Yangtze River Basin provinces, promote the scientific management of consumption reduction performance, and promote consumption reduction, this paper integrates the concept of low-carbon economy into the evaluation of consumption reduction performance of the Yangtze River Basin provinces. Combining the connotation of energy consumption reduction and low-carbon economy, this paper constructs a comprehensive and scientific evaluation index system for energy consumption reduction performance in the Yangtze River Delta region from three aspects: economy, energy, and environment. At the same time, the TOPSIS method and the full alignment polygon graphical index method are used to evaluate the energy consumption reduction performance of the Yangtze River Delta region from 2010 to 2020. Through the analysis, the following conclusions can be drawn: the overall performance level of energy consumption reduction in the Yangtze River Delta region is average; the coordination between economy, energy, and environment is poor. Through the gray correlation analysis of energy consumption reduction performance, it is found that the current energy consumption structure plays a decisive role in reducing energy consumption; therefore, energy consumption coefficient, industrial structure, and government incentives also play a key role in reducing energy consumption.